Determination of dehydroepiandrosterone and its biologically active oxygenated metabolites in human plasma evinces a hormonal imbalance during HIV-TB coinfection - Vecchione, María Belén (2018)
An estimated one third of the world's population is affected by latent tuberculosis (TB), which once active represents a leading cause of death among infectious diseases. Human immunodeficiency virus (HIV) infection is a main predisposing factor to TB reactivation. Individuals HIV-TB co-infected develop a chronic state of inflammation associated with hypothalamic-pituitary-adrenal (HPA) axis dysregulation. This results in a hormonal imbalance, disturbing the physiological levels of cortisol and dehydroepiandrosterone (DHEA). DHEA and its oxygenated metabolites androstenediol (AED), androstenetriol (AET) and 7-oxo-DHEA are immunomodulatory compounds that may regulate physiopathology in HIV-TB co-infection. In order to study possible changes in plasma levels of these hormones, we developed an approach based on high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). To our knowledge, this represents the first report of their simultaneous measurement in HIV-TB individuals and the comparison with healthy donors, obtaining statistically higher plasma levels of DHEA, AET and 7-oxo-DHEA in patients. Moreover, we found that concentrations of 7-oxo-DHEA positively correlated with absolute CD4+ T cell counts, nadir CD4+ T cell values and with individuals who presented TB restricted to the lungs. This research contributes to understanding the role of these hormones in HIV-TB and emphasizes the importance of deepening their study in this context.